2020
DOI: 10.1002/ppul.25080
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of antimicrobials in the treatment of cystic fibrosis pulmonary exacerbations:  II. Therapies for allergic bronchopulmonary aspergillosis

Abstract: This review is the second article in the State‐of‐the‐Art series and aims to evaluate medications used in the treatment of allergic bronchopulmonary aspergillosis (ABPA) in pediatric and adult patients with cystic fibrosis (CF). ABPA is one of several organisms that are found in the airways of CF patients. This review provides an evidence‐based summary of pharmacokinetic (PK)/pharmacodynamic (PD), tolerability, and efficacy studies of medications including corticosteroids, amphotericin B, azole antifungals (is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…CF, cystic fibrosis. fungus A. fumigatus destroys lung function if left untreated (8,24). In some patients the Spl-directed IgE response was very strong, and we propose that this could be an unrecognized cause of allergic lung exacerbation in CF patients harboring S. aureus in their airways.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…CF, cystic fibrosis. fungus A. fumigatus destroys lung function if left untreated (8,24). In some patients the Spl-directed IgE response was very strong, and we propose that this could be an unrecognized cause of allergic lung exacerbation in CF patients harboring S. aureus in their airways.…”
Section: Discussionmentioning
confidence: 84%
“…Prevention and therapy of chronic bacterial and fungal inflammation are therefore key in the treatment regimen of CF (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent studies have observed positive effects with voriconazole therapy in ABPA patients, in CF patients antifungal treatment varies widely across patients and centers (94). Drug interactions often preclude prolonged use of both azoles and CF medications, and the indeterminate clinical importance of treatment of A. fumigatus in CF further complicates treatment decisions (95).…”
Section: Discussionmentioning
confidence: 99%